Optimization of a three-row air-suction Brassica chinensis precision metering device based on CFD-DEM coupling simulation - Sun, Xinping; Li, Hua; Qi, Xindan; Feng, Dinghao; Zhou, Jianqi; Wang, Yongjian; Nyambura, Samuel Mbugua; Zhang, Xiaoyu; Chen, Xi (International Journal of Agricultural and Biological Engineering, 2023)
This study aimed to optimize a three-row air-suction Brassica chinensis precision metering device to improve the low seeding performance. ANSYS 17.0 Software was used to analyze the effect of different numbers of suction holes and different suction hole structures on the airflow field. It was found that a suction hole number of 60 was beneficial to the flow field stability and a conical hole structure was beneficial to the adsorption of seeds. Box-Behnken design experiments were carried out with negative pressure, rotational speed, and hole diameter as the experimental factors. The optimal parameter combination was achieved when the negative pressure was 3.96 kPa, the rotational speed of the seeding plate was 1.49 rad/s and the hole diameter was 1.10 mm. The qualification rate of inner, middle, and outer rings were 87.580%, 90.548%, and 90.117%, respectively, and the miss seeding rate of inner, middle, and outer rings were 10.915%, 7.139%, and 5.920%, respectively. Keywords: Brassica chinensis, metering device, airflow field, Box-Behnken design DOI: 10.25165/j.ijabe.20231603.7812 Citation: Sun X P, Li H, Qi X D, Feng D H, Zhou J Q, Wang Y J, et al. Optimization of a three-row air-suction Brassica chinensis precision metering device based on CFD-DEM coupling simulation. Int J Agric & Biol Eng, 2023; 16(3): 130–142.